2020
DOI: 10.1002/jbmr.4492
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Soluble Biomarkers for Fibrodysplasia Ossificans Progressiva (FOP) Reflect Acute and Chronic Inflammatory States

Abstract: Fibrodysplasia ossificans progressiva (FOP) is a progressive, debilitating genetic disease in which skeletal muscle and connective tissue is episodically replaced by heterotopic bone. Discovery of surrogate biomarkers of disease (genotype)-related and flare-up-associated activity of FOP in a readily accessible matrix, such as plasma, would facilitate an understanding of the complex pathophysiology of FOP, aid patient care, and provide a valuable tool for the development and monitoring of potential therapeutics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…FOP patients have chronically elevated levels of hyperinflammatory immune cells and pro-inflammatory cytokines 35,55,56 . FOP macrophages and mast cells are primed toward inflammatory responses 57 , and depletion of these cells reduces HO in mice 44 .…”
Section: Early Adulthood Treatment With Aav Gene Therapy Prevents Spo...mentioning
confidence: 99%
“…FOP patients have chronically elevated levels of hyperinflammatory immune cells and pro-inflammatory cytokines 35,55,56 . FOP macrophages and mast cells are primed toward inflammatory responses 57 , and depletion of these cells reduces HO in mice 44 .…”
Section: Early Adulthood Treatment With Aav Gene Therapy Prevents Spo...mentioning
confidence: 99%
“…Localized or systemic myopathy, chronic inflammation, atrophy, HO, prolonged immobilization or combination of factors could modulate the bioelectric properties of muscle tissue. An opportunity for further research may entail evaluation of EIM with other objective and more established methods such as imaging ( 18 F-NaF PET/CT, CT, X-Ray, and MRI) or quantification of circulating markers 18 , 33 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, soft tissue edema on MRI and 18 F-NaF-PET/CT activity are respectively associated with localized tissue inflammation and osteogenic activity typically associated with flares, but do not always correlate with the clinical course or predict sites of future HO 15 . To complement clinical and imaging data, recent studies have sought to identify disease and flare-up-associated biomarkers in plasma samples derived from patients with FOP 18 , which if validated in subsequent work, may provide a novel means to classify disease stages of FOP or further the understanding of mechanistic pathways implicated in FOP.…”
Section: Introductionmentioning
confidence: 99%
“…Our own research has revealed a significant increase in different cytokine levels, such as IL-3, IL-7, and IL-8 in the blood of patients with FOP [ 20 ] and has also shown that NF- κ B activation is a key factor for inflammation in FOP. Additionally, we have found that blood samples obtained from FOP individuals have high levels of proinflammatory interleukins even in the absence of flare-up symptoms [ 29 , 64 ]. We also found increased monocyte production of TGF-β in patients with FOP, consistent with findings in mouse models [ 63 ].…”
Section: The Role Of the Immune System In Fibrodysplasia Ossificans P...mentioning
confidence: 99%